Fuzzy Gain Scheduling of PID (FGS-PID) for Speed Control Three Phase Induction Motor Based on Indirect Field Oriented Control (IFOC) - Ferdiansyah, Indra; Purwanto, Era; Windarko, Novie Ayub (Politeknik Elektronika Negeri Surabaya (PENS), 2016)
This paper propose about using PID control system based on Kp, Ki, and Kd parameter determination with scheduling process from fuzzy logic. Control system is used to arrange speed of three phase induction motor using IFOC method. This method can be minimized the main problem from speed control of induction motor which is a transient condition. The robustness validation from this system use testing process of dynamic speed which is compared with the other control system to know the system performance in transient condition such as (rise time, overshoot, undershoot and settling time). The result shows using the proposed system has better performance responses which is requiring 0.001 seconds time in transient condition up to steady state condition without overshoot and undershoot problem.